2020
DOI: 10.3390/antibiotics9100716
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Property and Biocompatibility of Silver, Copper, and Zinc in Titanium Dioxide Layers Incorporated by One-Step Micro-Arc Oxidation: A Review

Abstract: Titanium (Ti) and its alloys are commonly used in medical devices. However, biomaterial-associated infections such as peri-implantitis and prosthetic joint infections are devastating and threatening complications for patients, dentists, and orthopedists and are easily developed on titanium surfaces. Therefore, this review focuses on the formation of biofilms on implant surfaces, which is the main cause of infections, and one-step micro-arc oxidation (MAO) as a coating technology that can be expected to prevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 108 publications
(129 reference statements)
2
67
0
1
Order By: Relevance
“…To empower dental implant osteoinduction, the titanium surface can be functionalized by coating it with a series of bioactive compounds and substances. For this purpose, various coatings have been proposed: nanoparticles of silver, copper, and zinc, as sanitizing agents, and antibacterial and bioactive substances [14], such as quaternary ammonium ions and chlorhexidine, antibiotics, or antimicrobial peptides [15]; calcium-phosphate alone [16] or hydroxyapatite or octacalcium phosphate complexes [17]. These substances are used to make the titanium surface bioactive to improve osteoinduction, by adding, in some cases, antibacterial properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To empower dental implant osteoinduction, the titanium surface can be functionalized by coating it with a series of bioactive compounds and substances. For this purpose, various coatings have been proposed: nanoparticles of silver, copper, and zinc, as sanitizing agents, and antibacterial and bioactive substances [14], such as quaternary ammonium ions and chlorhexidine, antibiotics, or antimicrobial peptides [15]; calcium-phosphate alone [16] or hydroxyapatite or octacalcium phosphate complexes [17]. These substances are used to make the titanium surface bioactive to improve osteoinduction, by adding, in some cases, antibacterial properties.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to different surgical protocols [10], geometry modifications [5,11] and various surface treatments for increasing surface roughness [1,12], such as acid-etching, grit-blasting, titanium plasma-spraying, or anodization [13], as well as the use of various coatings to make the titanium surface bioactive [14][15][16][17] are responsible for empowering the wettability, bone anchoring, and biomechanical stability between the implant-bone interfaces [3,6,10,12,18], thus increasing osteoinduction and osteointegration.…”
Section: Introductionmentioning
confidence: 99%
“…Such differences were attributed to possible dynamic bone formation and remodeling differences, especially in early healing intervals. A large number of in vitro and in vivo studies have revealed that, as well as good cytocompatibility, the addition of Sr and Ag to TiO 2 surfaces encourages strong antibacterial activity and accelerates new bone formation around the implant [ 47 , 48 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…When the antibacterial surface was soaked in normal saline for 28 days, the chemical states of the antibacterial active elements changed separately, leading to completely different changes in the antibacterial activity. The antimicrobial activity of the silver-coated specimens was gradually weakened, and Cu showed no significant change, while Zn showed enhanced antimicrobial activity [170].…”
Section: Comparisonmentioning
confidence: 95%
“…It is a necessary trace element in the human body and participates in the synthesis of enzymes. Cu is less cytotoxic than Ag [170] and can be metabolized by the human body. Therefore, Cu may be an effective substitute for Ag.…”
Section: Coppermentioning
confidence: 99%